Revisiting Ceriantharian (Anthozoa) Mitochondrial Genomes: Casting Doubts about Their Structure and Size. (26th June 2020) - Smith, David Roy
Abstract: Recently, Stampar et al. (2019 . Linear mitochondrial genome in Anthozoa (Cnidaria): a case study in. Sci Rep. 9(1):6094.) uncovered highly atypical mitochondrial genome structures in the cnidarian species Pachycerianthus magnus and Isarachnanthus nocturnus (Anthozoa, Ceriantharia). These two mitochondrial DNAs assembled as linear fragmented genomes, comprising eight and five chromosomes, respectively—architectures unlike any other anthozoan mitogenome described to date. What's more, they have cumulative lengths of 77.8 ( P. magnus ) and 80.9 kb ( I. nocturnus ), making them the largest animal mitochondrial DNAs on record, a finding which garnered significant attention by various news media. Here, I take a closer look at the work of Stampar et al. and question their key results. I provide evidence that the currently available mitogenome sequences for I. nocturnus and P. magnus, including their structures, sizes, and chromosome numbers, should be treated with caution. More work must be done on these genomes before one can say with any certainty that they are linear, fragmented, or the largest animal mitogenomes observed to date.